Diagnostic impact of integrated 18F-FDG PET/MRI in cerebral staging of patients with non-small cell lung cancer. (August 2017) - Deuschl, Cornelius; Nensa, Felix; Grueneisen, Johannes; Poeppel, Thorsten D; Sawicki, Lino M; Heusch, Philipp; Gramsch, Carolin; Mönninghoff, Christoph; Quick, Harald H; Forsting, Michael; Umutlu, Lale; Schlamann, Marc
Background: Integrated positron emission tomography/magnetic resonance imaging (PET/MRI) systems are increasingly being available and used for staging examinations. Brain metastases (BM) are frequent in patients with non-small cell lung cancer (NSCLC) and decisive for treatment strategy. Purpose: To assess the diagnostic value of integrated 18F-2-fluoro-2-deoxy-D glucose (18F-FDG) PET/MRI in initial staging in patients with NSCLC for BM in comparison to MRI alone. Material and Methods: Eighty-three patients were prospectively enrolled for an integrated 18F-FDG PET/MRI examination. The 3 T MRI protocol included a fluid-attenuated inversion-recovery sequence (FLAIR) and a contrast-enhanced three-dimensional magnetization prepared rapid acquisition GRE sequence (MPRAGE). Two neuroradiologists evaluated the datasets in consensus regarding: (i) present lesions; (ii) size of lesions; and (iii) number of lesions detected in MRI alone, compared to the PET component when reading the 18F-FDG PET/MRI. Results: Based on MRI alone, BM were detected in 15 out of the 83 patients, comprising a total of 39 metastases. Based on PET alone, six patients out of the 83 patients were rated positive for metastatic disease, revealing a total of 15 metastases. PET detected no additional BM. The size of the BM correlated positively with sensitivity of detection in PET. Conclusion: The sensitivity of PET in detection of BM depends on their size. 18F-FDG PET/MRI does not lead to an improvement in diagnostic accuracy in cerebral staging of NSCLC patients, as MRI alone remains the gold standard.